Design and Implementation of Web-Based E-Learning with W3C Standardization - Dewi, Ariyani Kusuma; Asyhab, Naufal; Yazid, Ahmad Subhan; Mulyanto, Agus (IJID (International Journal on Informatics for Development), 2013)
The development of Internet technology in education such as e-learning has increased significantly. This fact encourages schools to maintain the quality of education by applying e-learning. E- learning is one of the tools to improve the efficiency and effectiveness of performances in teaching and learning. But many e-learning schools do not comply with the standardization of World Wide Web Consortium (W3C). Standardizing the Web has been ignored by the developers of the system. When the W3C is used as a standardization of the system, such a system could be accessed through many browsers. E-learning is a web-based system which is developed using the programming language PHP, and XHTML document types to manage MySQL database. The method is used of system development, namely the System Development Life Cycle (SDLC). The system design method with a functional approach is described using the DFD (Data Flow Diagram). While the modeling of the data base is described by the ERD (Entity Relationship Diagram). E-learning web-based for the school of the W3C standardization is accessible in all browsers as well. E-learning supports the distribution (upload and download) data of the document contains. E-learning is also capable to display online and the results of value for the students, consequently it can help in the learning process.